Pulmonary Function in Post-Infectious Bronchiolitis Obliterans in Children: A Systematic Review and Meta-Analysis - Eun Lee; Suyeon Park; Hyeon-Jong Yang (Pathogens, 2022)
Owing to the rarity of post-infectious bronchiolitis obliterans (PIBO), pulmonary function in children with PIBO has been mainly investigated in small-sample sized studies. This systematic review and meta-analysis investigated pulmonary function in children with PIBO, regardless of age at respiratory insult and PIBO diagnosis. A systematic literature search revealed 16 studies reporting pulmonary function data in 480 children with PIBO. Levels of key pulmonary function parameters were summarized by pooled mean difference (MD) only in children with PIBO, and a random effect model was used. Pooled MDs (95% confidence interval [CI]) for FEV1, FVC, and FEF25–75% were 51.4, (44.2 to 58.5), 68.4 (64.4 to 72.3), and 26.5 (19.3 to 33.6) % predicted, respectively, with FEV1/FVC of 68.8% (62.2 to 75.4). Pooled MDs (95% CI) of the z-scores for FEV1, FVC, and FEF25–75% were −2.6 (−4.2 to −0.9), −1.9 (−3.2 to −0.5), and −2.0 (−3.6 to −0.4). Pooled MD (95% CI) for the diffusion capacity of the lungs for carbon monoxide from two studies was 64.9 (45.6 to 84.3) % predicted. The post-bronchodilator use change in the FEV1 in three studies was 6.1 (4.9 to 7.2). There was considerable heterogeneity across the studies. PIBO is associated with moderately impaired pulmonary function, and this review facilitates an understanding of PIBO pathophysiology in children.